2020
DOI: 10.32521/2074-8132.2020.2.055-073
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in adult human height of men and women in different regions of Russia since the end of the 19th to the beginning of the 21st century

Abstract: Ìèêðîýâîëþöèîííàÿ äèíàìèêà ïîêàçàòåëåé òåëîñëîaeåíèÿ â ïîïóëÿöèÿõ ÷åëîâåêà õàðàêòåðèçóåòñÿ çíà÷èòåëüíîé íåîäíîðîäíîñòüþ: ïåðèîäû óâåëè÷åíèÿ è óìåíüøåíèÿ òîòàëüíûõ ðàçìåðîâ òåëà öèêëè÷åñêè ñìåíÿëè äðóã äðóãà íà ïðîòÿaeåíèè âñåé èñòîðèè, íàïðàâëåííîñòü è òåìïû ñåêóëÿðíûõ èçìåíåíèé âàðüèðîâàëè â ðàçíûõ ãðóïïàõ [Stulp, Barrett, 2016; Niskanen et al., 2018]. Ê íàñòîÿùåìó âðåìåíè â íàó÷íîé ëèòåðàòóðå íàêîïëåíî îáøèðíîå êîëè÷åñòâî äàííûõ îá ýïîõàëüíîé âàðèàöèè ðàçìåðîâ òåëà (ãëàâíûì îáðàçîì, äëèíû è ìàññû òåëà) ó äåò… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(43 reference statements)
2
0
0
Order By: Relevance
“…The above results are consistent with research conducted by scientists from the Department of Anthropology of Moscow State University named after M. V. Lomonosov [53], who showed that despite the significant variability in secular changes in body size at different regions of Russia, a common pattern was identified for all populations, which consisted of an increase in definitive body length over the studied period of time. The analysis includes materials on body length for the adult population of 50 territorial subjects of the Russian Federation (34 regions, 9 republics, 6 territories, 1 autonomous district), surveyed from the end of the 19th to the beginning of the 21st century.…”
Section: Meat and Body Heightsupporting
confidence: 91%
See 1 more Smart Citation
“…The above results are consistent with research conducted by scientists from the Department of Anthropology of Moscow State University named after M. V. Lomonosov [53], who showed that despite the significant variability in secular changes in body size at different regions of Russia, a common pattern was identified for all populations, which consisted of an increase in definitive body length over the studied period of time. The analysis includes materials on body length for the adult population of 50 territorial subjects of the Russian Federation (34 regions, 9 republics, 6 territories, 1 autonomous district), surveyed from the end of the 19th to the beginning of the 21st century.…”
Section: Meat and Body Heightsupporting
confidence: 91%
“…The analysis includes materials on body length for the adult population of 50 territorial subjects of the Russian Federation (34 regions, 9 republics, 6 territories, 1 autonomous district), surveyed from the end of the 19th to the beginning of the 21st century. The average values of secular increases in definitive body length in the Russian population over the entire survey period were about 8 cm in men and over 4.5 cm in women, which is comparable to global values [53].…”
Section: Meat and Body Heightsupporting
confidence: 69%